In‐Plane BO3 Configuration in P2 Layered Oxide Enables Outstanding Long Cycle Performance for Sodium Ion Batteries. Issue 1 (21st November 2022) - Wang, Xuan; Dong, Xiping; Feng, Xiaochen; Shi, Qinhao; Wang, Jing; Yin, Xuemin; Zhang, Jiujun; Zhao, Yufeng
Abstract: P2‐phase layered cathode materials with distinguished electrochemical performance for sodium‐ion batteries have attracted extensive attention, but they face critical challenges of transition metal layer sliding and unfavorable formation of hydration phase upon cycling, thus showing inferior long cycle life. Herein, a new approach is reported to modulate the local structure of P2 material by constructing a state‐of‐the‐art in‐plane BO3 triangle configuration ((Na0.67 Ni0.3 Co0.1 Mn0.6 O1.94 (BO3 )0.02 ). Both are unveiled experimentally and theoretically that such a structure can serve as a robust pillar to hold up the entire structure, by inhibiting the H2 O insertion upon Na (de)intercalation and preventing the structure from deformation, which significantly boost the long cycle capability of P2‐materials. Meanwhile, more Na ions in the architecture are enabled to site on the edge sharing octahedrons (Nae ), thus benefiting the Na + transportation. Consequently, the as produced material demonstrates an ultralow volume variation (1.8%), and an outstanding capacity retention of 80.1% after 1000 cycles at 2 C. This work sheds light on efficient architecture modulation of layered oxides through proper nonmetallic element doping. Abstract : The new strategy of incorporating B can disrupt the Na + /vacancy ordering by regulating the ratio of Nae (edge sharing)/Naf (face sharing) sites and meanwhile prevent the H2 O insertion into the P2 crystal lattice upon cycling. Consequently, the as prepared Na0.67 Ni0.3 Co0.1 Mn0.6 O1.94 (BO3 )0.02 demonstrates improved electrochemical performance with a remarkable capacity retention (80.1%) over 1000 cycles.